PERAN TEKNOLOGI DALAM PENDIDIKAN AGAMA ISLAM - Afriandi, Afriandi; Riswandi; Ainun Mardiah; , Sahrul Adnan; Almira Humairah; Riska Damayanti; Rusmin (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
One element of education is teaching in schools, and many current educational problems arise from these elements, starting from the curriculum, the way lessons are delivered, to the condition and quality of teaching teachers. Even though there are many theories about teaching, these methods always experience obstacles in practice. One of them is student boredom in learning because learning methods and learning places tend to bore students. Educational technology seeks to solve and/or facilitate the solving of lifelong human learning problems, where, when, how, and by anyone. Learning problems can be found at home, at school, in places of worship, at work, and in society. By developing one of the principles of educational technology